FAKTOR-FAKTOR YANG MEMPENGARUHI KONSUMEN DALAM MEMILIH PERUMAHAN (STUDI KASUS: PERUMAHAN VILLA CITRA DAN VILLA BUANA GARDENIA) - Zamzami Zamzami; Abdullah Abdullah; Hafnidar A. Rani (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2018)
The city of Banda Aceh, apart from being the administrative center of Aceh's administration, is also a center of economic, educational and trade activities, so that economic growth and population are growing rapidly. Consumer preferences in choosing housing varies greatly, because every individual has different desires in choosing the desired housing. The purpose of this study is to determine the preferences of consumers in choosing and determine the desired housing. Based on the result of correlation analysis, that the quality factor/character of social environment (Xe6) correlation between consumer preferences in choosing Villa Citra housing equal to R = 0,358 shows "low" relationship level while consumer preferences in choosing Villa Buana Gardenia housing show value equal to R = 0,585 show level of relationship "moderate or moderate". Multiple linear regression analysis obtained significant value that is in variable (Xe7) equal to 0,066 or in "condition and shape of house" while for Villa Villa Gardenia from multiple linear regression analysis obtained value of regression coefficient that is at variable (Xi4) equal to 0,006 that is or on "motivation to stay" and the variable (Xi5) of 0.038 is the quality/character of the social environment. This shows that the relationships in these variables have significant relationship values.